The design of a Probability Bidding Mechanism in electricity auctions by considering trading constraints. (October 2015) - Han, Dun; Sun, Mei
In the electricity trading exchange, we need to consider electricity price, transmission costs, network congestion and technology constraints. Therefore, some electricity trading may be forced to be canceled because of limits on power transmission lines. The most challenging issue is how to make an appropriate auction bidding mechanism in electricity trading. According to the bipartite network and evolutionary game theory with the Paid-as-Bid auction mechanism as research background, we explore a Probability Bidding Mechanism (PBM). The designed mechanism could significantly disrupt the learning process and weaken the unconscious collusion behaviors of generators during the auction process. The simulation results of the proposed mechanism are compared with the High–Low Matching bidding mechanism and the comparison shows that the PBM could minimize the average transaction price and maximize the average trading quantities effectively. Further investigation reveals that the parameter, which is used to adjust trading price, has more influence on generators than purchasers. Some suggestions for reducing the generator's offer and increasing the market trading quantities are recommended at the end of the paper.